Visualization and analysis of word co-occurrence network of the articles of the Journal of Applied Psychology - مهدی رحمانی (فصلنامه روان‌شناسی کاربردی, 2018)
Aim: The study purpose was visualization and analysis of word co-occurrence network of Journal of Applied Psychology of Shahid Beheshti University. Method: Research method was descriptive and using scientometric indices and social network analysis using a purposeful method. Research population consisted of all articles published in the mentioned Journal during period of 2015-16 (N= 287). Title, abstract and key words of 287 articles were reviewed and categorized under the guidance of two psychologists in various subject areas. In the next step, adjacency matrix of conjugate terms of extracted words was obtained in Excel software. Finally, data was generated using the U.S.I.Net software. She. S Vivor was analyzed. Results: Results showed that domains of cognitive psychology, social issues, emotion and personality have been of great importance in this Journal. Most articles in the Journal of Applied Psychology have been published in the field of cognitive psychology. In addition, the results showed that self-efficacy, coping styles, and adaptability had the highest degree of centrality degree and the components of subjective well-being, self-efficacy, adaptability and social dimensions were the most important indicator of the centrality of vision. Conclusion: The presentation of the thematic map of the articles in the journal of applied psychology will make the researchers more aware of the status of the researchers conducted and their relationship with the knowledge of the subject's gaps and help researchers to understand the general view of the scientific framework of the field of psychology and help researchers to select hot topics in this area